Long-Term Effects of Law Enforcement's Post-9/11 Focus on Counterterrorism and Homeland Security, 2007-2010, United States - Davis, Lois M. ([Verlag nicht ermittelbar], 2014)
This study examines the state of counterterrorism and homeland security in five large urban law enforcement agencies (the Boston Police Department, the Houston Police Department, the Las Vegas Metropolitan Police Department, the Los Angeles County Sheriff's Department, and the Miami-Dade Police Department) nine years following the September 11, 2001, terrorist attacks. It explores the long-term adjustments that these agencies made to accommodate this new role. Researchers from the RAND Corporation, in consultation with National Institute of Justice project staff, selected law enforcement agencies of major urban areas with a high risk of terrorist attacks from different regions of the United States that have varied experiences with counterterrorism and homeland security issues. The research team conducted on-site, in-depth interviews with personnel involved in developing or implementing counterterrorism or homeland security functions within their respective agency. The research team used a standardized interview protocol to address such issues as security operations, regional role, organizational structures, challenges associated with the focus on counterterrorism and homeland security issues, information sharing, training, equipment, and grant funding.